The evolving landscape and research trend of calcitonin gene-related peptide in migraine: A bibliometric analysis and visualization - Wang, Liwei; Wang, Qing; Diao, Huaqiong; Liu, Xueying; Zhao, Yonglie (Frontiers in Neurology, 2024)
Background Migraine is a global public health concern, affecting both social and individual well-being. Calcitonin gene-related peptide (CGRP), a crucial neuropeptide, holds important research value in understanding migraine pathogenesis. CGRP receptor antagonists and monoclonal antibodies that target CGRP or its receptors have shown efficacy in reducing migraine frequency and severity, presenting a promising therapeutic approach. This study aimed to conduct a comprehensive bibliometric analysis to analyze the current state, research trends, and future directions of CGRP in migraine. Methods Bibliometric tools including CiteSpace, VOSviewer, etc., were utilized to extract and summarize publications related to CGRP in migraine from the Web of Science Core Collection Database (WOSCC) between 2004 and 2023, as of December 31, 2023. The analysis focused on trends in annual publications, leading countries/regions and institutions, prominent journals and references, influential authors, and high-frequency keywords in the field. Results A total of 1,821 articles and reviews involving 5,180 authors from 1,315 organizations across 64 countries were included in the study. These publications were distributed across 362 journals and accumulated 56,999 citations by December 31, 2023. An increasing trend was observed in annual publications on CGRP in migraine. The United States emerged as the leading nation in both publications and citations, with academic Peter Goadsby contributing the highest number of publications. The University of Copenhagen stood out as the institution with the most publications, and Cephalalgia emerged as the most influential journal. The most cited paper identified was “Calcitonin gene-related peptide receptor antagonist BIBN4096BS for the acute treatment of migraine” by Jes Olesen, published in the New Engl Med. Keyword frequency analysis revealed prevalent terms such as “migraine,” “CGRP,” and “episodic migraine,” along with emerging topics represented by keywords including “trial,” “monoclonal antibodies,” “preventive treatment,” and “safety.” Conclusion CGRP is pivotal in migraine pathogenesis, and there is a robust research foundation exploring its role. The US leads in research output on CGRP in migraine. Investigating the mechanism of CGRP and its receptor in migraine remains a key area of interest, particularly focusing on signaling pathways. Future research should target identifying critical therapeutic targets in CGRP antagonist pathways for migraine treatment.